SOCIAL ECONOMIC INTEGRATION IN ACEH: PRIOR-POST TSUNAMI - Ardi Adji (Widyariset, 2011)
The aims of this paper is to analyze the social economic linkages among region, means intra-interre-gional of Aceh province during prior-post tsunami reconstruction and recovery. The social economy destruction caused by the earthquake and tsunami had brought massively impact to the Acehnese welfare. Based on the facts stated above, it is very crucial to observe and measure the social economic sectors development among regions as an impact of infrastructure development and social economic integration that focus on three main regions, namely, Ladiagalasska (Indian Ocean, Gayo Alas Singkil, and the Malacca Strait). In addition to that, each of region has a different effect and correlation significantly. The research methodology applied the Multiregional Input-Output (MRIO) in term to set up MRIO Aceh 2002 and 2006 and descriptive analysis. The research found the increase social integration intra-region in Aceh the and decrease of trading among regions post tsunami attack.